Testamentary formalities - Reid, Kenneth (Kenneth G. C.); De Waal, M. J. (Marius Johannes); Zimmermann, Reinhard, 1952 Oct. 10- (Oxford : Oxford University Press, 2011)
Launching a major new research project examining the principles of succession law in comparative perspective, this volume analyses the formalities imposed by the law on making a will across a wide range of European and international jurisdictions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wills